Spectral analysis of acoustic emission signals generated by twinning and shear band formation in silver single crystals subjected to channel-die compression tests - Ranachowski, Zbigniew; Piątkowski, A.; Pawełek, A.; Jasieński, Z. (Archives of Acoustics, 2006)
In the paper there are presented the results of investigations of the relations between acoustic emission (AE) and the mechanisms of twinning as well as shear band formation and propagation in silver single crystals of {112} orientation, subjected to channel-die compression tests at ambient temperature. The results were obtained using an AE analyzer of a new generation, installed recently at the Institute of Metallurgy and Materials Sciences, and were compared with those obtained also for single Ag crystals of the same orientation, tested at the room and at liquid nitrogen (−196^°C) temperatures, but registered applying an AE analyzer of older generation, used until now. The results of AE measurements obtained using the new analyzer allowed to plot the acoustograms produced with the application ofWindowed Fourier Transform method for analysis of large experimental data sets (4×132 Msamples). This allowed the authors to solve the problem of identification of the strain mechanisms leading to formation of different dislocation systems.